2020
DOI: 10.1289/ehp6386
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation and the Association between Maternal Airborne Particulate Matter Exposure and Preterm Delivery: A National Birth Cohort Study in China

Abstract: Background: Potential modification of the association between maternal particulate matter (PM) exposure and preterm delivery (PTD) by folic acid (FA) supplementation has not been studied. Objective: We examined whether FA supplementation could reduce the risk of PTD associated with maternal exposure to PM in ambient air during pregnancy. Method: In a cohort study covering 30 of the 31 provinces of mainland China in 2014, 1,229,556 primiparas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Recent findings suggest a potential protective effect of folic acid, an antioxidant component of the diet; against effects of phthalate metabolites, 22 pesticides 23 and air pollutants 24 on autistic traits 24 and intellectual abilities in children, 25 or on the risk of preterm birth. 26 However, to our knowledge, no study evaluated similar patterns for other environmental contaminants on cognitive performance among the elderly. In this investigation, we hypothesized that a high-diet quality or adherence to an anti-inflammatory dietary pattern may attenuate inflammation and subsequently reduce the metals-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 97%
“…Recent findings suggest a potential protective effect of folic acid, an antioxidant component of the diet; against effects of phthalate metabolites, 22 pesticides 23 and air pollutants 24 on autistic traits 24 and intellectual abilities in children, 25 or on the risk of preterm birth. 26 However, to our knowledge, no study evaluated similar patterns for other environmental contaminants on cognitive performance among the elderly. In this investigation, we hypothesized that a high-diet quality or adherence to an anti-inflammatory dietary pattern may attenuate inflammation and subsequently reduce the metals-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 97%
“…FA supplementation has been shown to attenuate MDCassociations (i.e. air pollutants, phthalates) with adverse birth [15] and neurodevelopmental outcomes, [16] but its potential modifying role in MDC associations with liver injury has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The program aimed to motivate 70% of women to commence folic acid supplementation at least three months before conception ( 3 - 4 ). However, studies have indicated suboptimal adherence levels (below 40%), significantly short of the MOH’s target ( 5 - 6 ), though the degree of adherence noticeably improved with higher maternal educational levels ( 6 ). This study investigates the use of folic acid, its protective effect against NTDs, and the significant features influencing adherence to the supplementation protocol in five counties within China’s Shanxi Province following the rollout of the national supplementation program.…”
mentioning
confidence: 99%